Pengembangan Bahan Ajar Bangun Datar Kelas 4 Pendekatan Open-Ended Untuk Meningkatkan Penalaran Di SD - Hidayah Sri Murwati; Joko Sulianto; Aries Tika Damayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background of this research and development is the teaching materials used in elementary schools havenâ€™t motivated students to learn mathematics, especially those related to teaching materials for flat shapes that can improve students' reasoning based on open-ended approach. The purpose of this study was to determine the availability of teaching materials in elementary schools and steps for developing flat shapes teaching materials to improve reasoning. The type of research used the Research and Development (RnD) Borg and Gall model. The data analysis technique used descriptive qualitative. The results ofÂ  feasibility assessment material expert validation stage 1 obtained a percentage 51.25% categorized "Fair enough and revised", stage 2 validation experienced an increase of 97.5% categorized "very feasible and without revision". Media validation stage 1 obtained results 58% categorized "adequate and revised", stage 2 validation experienced an increase 85% categorized "adequate and without revision". The results of a field trial on grade 4 teachers SDN Jomblang 02 Semarang assessing the content of material, namely 89.85% categorized "appropriate and without revision" and results validation structure teaching materials by 85% categorized "appropriate and without revision". Flat shape teaching materials based on open-ended approach improve students' reasoning, meet the criteria and are suitable for use in learning.